The grammar of English reflexives - Helke, Michael, 1943- (Routledge library editions. English language, 2015)
This work, first published in 1979, was a doctoral dissertation submitted to the Department of Foreign Literatures and Linguistics of the Massachusetts Institute of Technology in 1970. The first chapter of this thesis concerns the supposed complementarity of reflexives and ordinary anaphoric pronouns. In the second chapter a theory of reflexivisation is characterised which encompasses several other theories. The third chapter considers apparent counter-examples to the generalizations regarding reflexives that were established in Chapter Two. The fourth chapter concerns the meaning of reflexive.